Barriers to management of Chronic Kidney Disease (CKD) CKD in a renal clinic in KwaZulu-Natal Province, South Africa - A qualitative study - Geldine Chironda; Busisiwe Bhengu (Elsevier, 2019)
Background: The progression of Chronic Kidney Disease (CKD) and existence of comorbid conditions makes management of CKD complicated, leading to unforeseen challenges for patients and healthcare professionals. Moreover, studies exploring the barriers to management of CKD from the perspectives of healthcare workers involved in direct care or patients receiving such care are limited. Purpose of the study: The purpose of this study was to explore the barriers to management of CKD in a Renal Clinic in KwaZulu-Natal Province, South Africa. Methods: A qualitative research approach was used, and a descriptive exploratory design employed. The sample size was thirteen, with seven CKD patients and six healthcare providers, as determined by data saturation. A purposive sampling strategy was used to select study participants. Semi-structured interviews with open-ended questions were utilised to collect the data. Credibility, transferability, confirmability and dependability were used to evaluate the trustworthiness of the qualitative data collected. Data was analysed using a thematic framework approach. Ethical rights were observed, and informed consent and participant authorisation were sought. Results: The side-effects of treatment, longevity of haemodialysis procedure, gastrointestinal problems, a false sense of good health, depression, lack of employment opportunities, limited in-service training, inclement weather condition, cultural and religious practices as well as uncertainties about obtaining a kidney transplant were highlighted as barriers to the management of CKD from the perspectives of both CKD patients and healthcare workers. Conclusion: Despite the measures of state hospitals to provide CKD management, barriers to management of CKD still exist amongst the CKD population. Hence, there is need to develop specific tailored interventions to reduce such obstacles thus promoting effective management of CKD patients. Keywords: Barriers, Management, Chronic Kidney Disease, Healthcare workers, Patients